Promoting Open, Flexible and Distance Learning in Increasingly Challenging Times - Niki Davis; Alison Fields; Maggie Hartnett (Flexible Learning Association of New Zealand, 2016)
Although the potential to increase equitable access to education is threatened by economic and technical developments, the Journal of Open, Flexible and Distance Learning is working to address these threats. This editorial describes actions over the lifetime of one leader in the field and the lifetime of this journal. Our move to align with and take advantage of the Public Knowledge Project in Canada is the most recent action. The articles and book reviews in this issue also provide a number of illustrations of the open scholarship that is working to increase equitable access for adults and children in this region and around the world.